2014
DOI: 10.1051/swsc/2014019
|View full text |Cite
|
Sign up to set email alerts
|

GPS scintillation effects associated with polar cap patches and substorm auroral activity: direct comparison

Abstract: We directly compare the relative GPS scintillation levels associated with regions of enhanced plasma irregularities called auroral arcs, polar cap patches, and auroral blobs that frequently occur in the polar ionosphere. On January 13, 2013 from Ny-Å lesund, several polar cap patches were observed to exit the polar cap into the auroral oval, and were then termed auroral blobs. This gave us an unprecedented opportunity to compare the relative scintillation levels associated with these three phenomena. The blobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(149 citation statements)
references
References 31 publications
10
139
0
Order By: Relevance
“…The GPS signal loss of Swarm satellites at high latitudes is also believed to be caused by the irregularities. These high-latitude plasma irregularities, including polar cap patches occurring inside the polar cap (Crowley, 1996;Clausen and Moen, 2015) and auroral blobs at aurora latitudes (Crowley et al, 2000;Jin et al, 2014), can be created directly/indirectly by particle precipitations (Kelley et al, 1982) or through the convection of dayside plasma into the polar cap (Foster et al, 2005;Stolle et al, 2006b). To check if the high-latitude GPS signal loss also depends on the amplitude of plasma gradients, we further analyzed Swarm in situ plasma density measurements.…”
Section: Gps Signal Loss Event Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPS signal loss of Swarm satellites at high latitudes is also believed to be caused by the irregularities. These high-latitude plasma irregularities, including polar cap patches occurring inside the polar cap (Crowley, 1996;Clausen and Moen, 2015) and auroral blobs at aurora latitudes (Crowley et al, 2000;Jin et al, 2014), can be created directly/indirectly by particle precipitations (Kelley et al, 1982) or through the convection of dayside plasma into the polar cap (Foster et al, 2005;Stolle et al, 2006b). To check if the high-latitude GPS signal loss also depends on the amplitude of plasma gradients, we further analyzed Swarm in situ plasma density measurements.…”
Section: Gps Signal Loss Event Detectionmentioning
confidence: 99%
“…Ionospheric scintillations from ground-based measurements have been widely used to investigate the morphology of the ionosphere (e.g., Basu et al, 1980;Aarons, 1982;Spogli et al, 2009;Jin et al, 2014;Clausen et al, 2016). Some low Earth orbit (LEO) missions, such as the CHAllenging Minisatellite Payload (CHAMP) and the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC), were equipped with GPS radio occultation (RO) instruments with high temporal resolution, which have also been applied for investigating the morphology of Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…We note that in the global view of this event in the paper by Cherniak et al (2015), patches were observed to drift across the polar cap and enter the nightside auroral oval, and they were associated with significant increases in the intensity of ionospheric irregularities. In a case study of another event by Jin et al (2014), patches that had entered the auroral region (auroral blobs) were directly connected to the strongest scintillations. In the case study by van der Meeren et al (2015), scintillations were not observed for patches outside of the region of auroral emissions/particle precipitation, but strong scintilllation was observed in association with patches co-located with strong auroral emissions/particle precipitation.…”
Section: Auroral Electrojetmentioning
confidence: 99%
“…Weber et al 1986;Krankowski et al 2006;Kintner et al 2007;Tiwari et al 2010;Moen et al 2012;Prikryl et al 2013;Jin et al 2014). They are either transported across the polar cap from the dense ionospheric plasma at the sunlit side of the Earth or created by particle precipitation in the cusp.…”
Section: Introductionmentioning
confidence: 99%
“…Charged particles from the solar wind and magnetosphere, mostly electrons and protons, precipitate in the upper atmosphere and dissipate their energy by generating the auroral emission. The nightside auroral events have been studied by many researchers since the last several decades and it has been found that in the auroral region, strong ionospheric scintillations are observed (Coker et al, 2004;Mitchell et al, 2005;De Franceschi et al, 2008;Hosokawa et al, 2014;Jin et al, 2014;van der Meeren et al, 2014van der Meeren et al, , 2015; and the references therein). Cusp region ionospheric irregularity dynamics which gives rise to pre-noon hour scintillation and cycle slips have been found to be associated with the polar cap patches during the solar minimum (Prikryl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%